ボストーク コア ニ フクマレル クラスレート スイワブツ ノ ケッショウ ガク テキ カイセキ - 本堂, 武夫; ホンドウ, タケオ; 内田, 努; ウチダ, ツトム; 前, 晋爾; マエ, シンジ; Duval, P.; Lipenkov, V. YA.; Hondoh, Takeo; Uchida, Tsutomu; Mae, Shinji; Lipenkov, V.Ya. (1992)
P(論文) 南極ボストークで掘削された深層ボーリング・コアの解析, 特にクラスレート水和物の解析について, その方法と今後の解析計画を紹介する。クラスレート水和物は, 水分子を骨格として, 空気を分子レベルで取り込んだ結晶であり, 氷床深部において気泡の消失と共に出現する。本稿では, X線回折およびラマン散乱の測定によって明らかにされたクラスレート水和物の結晶学的構造を説明すると共に, 氷床におけるその生成過程を考察する。また, 気候変動との関連におけるクラスレート水和物の重要性, ならびにその解析が新たなコア解析手法として, どんな情報をもたらすかについて現時点での知見を基に説明する。 Purpose and methods of crystallographic analyses of clathrate hydrates included in ice cores recovered at Vostok, Antarctica are briefly reviewed. The clathrate hydrate is a crystal composed of a cage structure formed by water molecules, and includes individual air molecules in the molecular cages. We describe the crystallographic structure of the clathrate hydrate crystals found in deep ice cores determined by X-ray diffraction and Raman scattering measurements, and discuss the formation process of the crystals in the ice sheet. We also discuss, as a future prospect in core analysis, what new information and knowledge relating to climatic changes can be deduced from the crystallographic analysis of the clathrate hydrates. departmental bulletin paper